2017
DOI: 10.18172/cig.3211
|View full text |Cite
|
Sign up to set email alerts
|

Mass soil movement on terraced landscapes of the Mediterranean mountain areas: a case study of the Iberian Range, Spain

Abstract: ABSTRACT. Terraces represent one of the most common agricultural landscapes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…First, when no longer adequately maintained, terraced slopes can become very hazardous environments. In literature, this negative trend was extensively documented in various Mediterranean terraced areas, where many researchers observed that hydrological and geomorphic processes are favoured by land abandonment and that these phenomena contribute to soil depletion issues (Arnáez et al, ; Arnáez, Lana‐Renault, Ruiz‐Flaño, Pascual, & Lasanta, ; Freppaz et al, ; García‐Ruiz & Lana‐Renault, ; Koulouri & Giourga, ; Lasanta et al, ; Lesschen et al, ; Stanchi, Freppaz, Agnelli, Reinsch, & Zanini, ). On the other hand, as observed in other environments (Cammeraat, van Beek, & Kooijman, ; Latocha, ), increasing time since abandonment the beneficial effect of vegetation cover becomes increasingly effective in preventing erosion and landsliding.…”
Section: Resultsmentioning
confidence: 98%
“…First, when no longer adequately maintained, terraced slopes can become very hazardous environments. In literature, this negative trend was extensively documented in various Mediterranean terraced areas, where many researchers observed that hydrological and geomorphic processes are favoured by land abandonment and that these phenomena contribute to soil depletion issues (Arnáez et al, ; Arnáez, Lana‐Renault, Ruiz‐Flaño, Pascual, & Lasanta, ; Freppaz et al, ; García‐Ruiz & Lana‐Renault, ; Koulouri & Giourga, ; Lasanta et al, ; Lesschen et al, ; Stanchi, Freppaz, Agnelli, Reinsch, & Zanini, ). On the other hand, as observed in other environments (Cammeraat, van Beek, & Kooijman, ; Latocha, ), increasing time since abandonment the beneficial effect of vegetation cover becomes increasingly effective in preventing erosion and landsliding.…”
Section: Resultsmentioning
confidence: 98%
“…Arnaéz et al . (in press) have verified in the Iberian system (Spain) that the abandoned terraces provide abundant sediments to the channels, because their abandonment implies changes in the distribution of the saturated areas and the drainage networks, and the possibility that small mass movements are activated. They calculate that more than 50% of the walls of the terraces have been mobilised either by landslides or by stone falls, with important volumes of material mobilised.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of farmland abandonment on terraced landscapes are manifold, because these areas have been conditioned by disturbances in topography and soil characteristics (Seeger and Ries, 2008) established during terrace construction. In addition to the recovery of vegetation, the lack of maintenance resulting from farmland abandonment may cause failures in the terrace risers, often followed by small mass movements and gullying (Lesschen et al, 2008;Solé-Benet et al, 2010;Arnáez et al, 2015Arnáez et al, , 2017, resulting in new sediment sources on the hillslopes. The off-site effects of these phenomena, which depend on the spatial distribution of sediment sources, water transfer paths and local sinks, are still unclear, due in part to the lack of studies that have investigated the hydrology of abandoned terraced landscapes, especially at the catchment scale.…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 99%